Resistência e negritude: experiências de enfrentamento ao racismo de jovens negros universitários - Spindola, Carine dos Santos (Universidade Federal de São Carlos, 2022)
This study aimed to analyze the academic and personal trajectories of young black college students. This is a qualitative approach study. The study was approved by the Ethics Committee on Human Research of the Universidade Federal de São Carlos (Opinion No. 5.012.198, CAAE No. 48525521.0.0000.5504). Two interview sessions based on a semi-structured script were conducted with three university students. In the interviews, the participants' experiences of racism were investigated, as well as their life stories, experiences of resistance to racism, and relationship with the university. The collected data were analyzed by means of Inductive Thematic Analysis. Three categories emerged from the analysis: identity, racial discrimination, and resistance to racism. Resistance was an instrument of power exercised by all participants throughout their trajectories. The discussion of racism at the university and by the Psychology area is important for the construction of anti-racist institutions.
Resistance and blackness: experiences in confronting racism of young black university students
Keywords: Racismo; Jovens universitários; Identidade; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO